Influence and mechanisms of active silica in solid waste on hydration of tricalcium aluminate in the resulting composite cement. (June 2021) - Zheng, Dapeng; Cui, Hongzhi; Tang, Waiching; Sang, Guochen; Lo, Tommy Y.
Abstract: Many industrial solid wastes are rich in silica (SiO2 ) which can be used as supplementary cementitious material (SCM) to replace part of Portland cement. Existing studies mainly focus on the impact of solid waste on tricalcium silicate (C3 S) hydration. Since tricalcium aluminate (C3 A) is the most reactive component of the Portland cement, it is of great interest t to investigate the effect of solid waste containing SiO2 on the hydration process of C3 A. In this study, different amounts of nano-silica (nano-SiO2 ) were mixed with C3 A and the hydration products after 72 h of hydration were analyzed by means of X-ray diffraction (XRD), Fourier Transform Infrared analyzer (FT-IR), Environment Scanning Electronic Microscope - Energy Dispersive Spectrometer (ESEM-EDS), X-ray Photoelectron Spectroscopy (XPS) and Solid-state Nuclear Magnetic Resonance (NMR). The results showed that nano-SiO2 can promote the hydration of C3 A and stabilize the hydration products of C3 A in the form of crystalline hydrogarnet (C3 AH6 ). The formation of Si-O-Al bonds was also found in the hydration products. ESEM results revealed that the surface of the crystalline hydration products (C3 AH6 particles) was covered by gel-like products. The results from the XPS and NMR analyses further confirmed that the negatively charged nano-SiO2 and the silicate anions can literally interact with C3 A to produce calcium silicoaluminate hydrate (C-A-S-H) gel, whereas the formation of C-A-S-H is attributed to the substitution reaction of Al in the Si-O-Si network occurring on the surface of C3 A. In addition to the reactive silica-aluminum component reacting with Ca(OH)2 to form additional calcium silicate hydrate (C-S-H) and C-A-S-H gels, the reactive silicon in solid waste can also undergo pozzolanic reaction with C3 A to form C-A-S-H gel.